2009
DOI: 10.1073/pnas.0905281106
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary structure of the human Cdt1-Geminin complex regulates DNA replication licensing

Abstract: All organisms need to ensure that no DNA segments are rereplicated in a single cell cycle. Eukaryotes achieve this through a process called origin licensing, which involves tight spatiotemporal control of the assembly of prereplicative complexes (pre-RCs) onto chromatin. Cdt1 is a key component and crucial regulator of pre-RC assembly. In higher eukaryotes, timely inhibition of Cdt1 by Geminin is essential to prevent DNA rereplication. Here, we address the mechanism of DNA licensing inhibition by Geminin, by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(112 citation statements)
references
References 42 publications
3
97
0
12
Order By: Relevance
“…Interestingly, although several amino acids important for Cdt1 binding (20,23) are conserved in the Idas coiled-coil region, Idas does not interact with Cdt1 either in cells or in vitro. This lack of interaction between Idas and Cdt1 highlights residues on the primary Geminin-Cdt1 interface that could be essential for a stable interaction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, although several amino acids important for Cdt1 binding (20,23) are conserved in the Idas coiled-coil region, Idas does not interact with Cdt1 either in cells or in vitro. This lack of interaction between Idas and Cdt1 highlights residues on the primary Geminin-Cdt1 interface that could be essential for a stable interaction.…”
Section: Discussionmentioning
confidence: 98%
“…Vectors were transformed to Rosetta-2 cells (Novagen) and grown in the presence of a suitable antibiotic. For co-expression experiments, Idas plasmids were simultaneously transformed together with Geminin plasmids (23) in the presence of suitable antibiotics. Protein production was induced with isopropyl 1-thio-␤-D-galactopyranoside at 15°C at an optical density of ϳ0.8, and cells were left to grow for an additional 16 -18 h at 15°C.…”
Section: Methodsmentioning
confidence: 99%
“…These models of how licensing is permitted in the presence of geminin are not mutually exclusive. Several structural studies of Cdt1-and geminin-domains, alone and in complex, support the idea of different stoichiometries of the Cdt1-geminin complex (Lee et al, 2004), (Okorokov et al, 2004), (De Marco et al, 2009). …”
Section: Gemininmentioning
confidence: 89%
“…As Cdt1 levels increase, geminin co-localizes with Cdt1 in the nucleus. Earlier work has shown that a Cdt1-geminin complex is functional for licensing (39,40) and that the stoichiometry of Cdt1 and geminin (39) as well as structural changes (40) dictate permissive versus inhibitory licensing activity of the complex. These data allow us to speculate that this control mechanism over geminin balances the levels of geminin in the nucleus to the levels of Cdt1, permitting licensing when cells transit from quiescence to G 1 (Fig.…”
Section: Discussionmentioning
confidence: 99%